A Compact Reflectionless Low-Pass Filter Based on TSV Technology. Issue 1 (1st November 2022) - Wang, Fengjuan; Wang, Rui; Li, Ruiqi; Yu, Ningmei; Yang, Yuan
Abstract : This paper presents a compact reflectionless low-pass filter based on through-silicon via (TSV). Its overall structure is composed of TSV inductors and redistribution layer(RDL) capacitor. The high-frequency structure simulator (HFSS) validates the proposed reflection filter. The results show that the filter operates at a frequency of 0-6.6GHz, with The return loss of input and output is less than -14.6dB in all test frequency bands(0-30GHz). In addition, the size of the reflectionless filter is only 0.19×0.23×0.0139 mm 3 (0.014× 0.017×0.01 λ g 3 ).